Outdoor Education Fatalities in Canada: A Comparative Case Study - Jackson, Jeff; Priest, Simon; Ritchie, Stephen (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2023)
The recent criminal negligence case against an Ontario teacher in the death of a student identified pertinent outdoor education administration and policy issues. This comparative case study examined this case and two additional high profile Canadian outdoor education fatalities, identifying common factors and issues. Using Accimaps to illustrate the multiple contributing factors for each event, the case studies all exhibited contributory administrative factors of undefined risk tolerance, risk creep, lack of oversight, and issues regarding parental consent. Conclusions were drawn as preventative lessons that can inform school or board-level outdoor education policy and practice.